Advanced Fetal Cardiac Anomaly Diagnosis with Multispectral LBP Transformation Techniques and Deep Learning Models - M. O., Divya; VIjaya, M. S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research is dedicated to developing an advanced deep learning diagnostic model capable of accurately diagnosing fetal cardiac anomalies in real-time ultrasound scan images. To achieve this, the dataset utilized in the previous research has undergone a transformation using Multispectral Local Binary Pattern (MLBP) and Adaptive Multispectral Local Binary Pattern (AMLBP) techniques. Local Binary Pattern (LBP) is an essential texture image feature, and MLBP and AMLBP are enhanced versions designed to capture intricate local structures and patterns within each image. Unlike the traditional LBP transformation, MLBP and AMLBP take color channels into account, allowing for more comprehensive feature extraction from the input images. The previously formed FetalEcho_V05 dataset has been transformed into two distinct datasets: FetalEcho_V0502 using MLBP and FetalEcho_V0503 using AMLBP. Both of these datasets are then employed in training customized versions of AlexNet, custom CNN(CCNN), VGG16, and ResNet50 deep learning (DL) models to create powerful classifiers. Among all the models, CCNN model demonstrated the best performance on the FetalEcho_V0503 dataset, showcasing its superiority in accurately diagnosing fetal cardiac anomalies from real-time ultrasound scan images.